The effects of corticosteroids on COPD lung macrophages: a pooled analysis - Higham, Andrew (Respir Res, 2015)
BACKGROUND: There is large variation in the therapeutic response to inhaled corticosteroids (ICS) in COPD patients. We present a pooled analysis of our previous studies investigating the effects of corticosteroids on lung macrophages, in order to robustly determine whether corticosteroid sensitivity in COPD cells is reduced compared to controls, and also to evaluate the degree of between individual variation in drug response. METHODS: Data from 20 never smokers (NS), 27 smokers (S) and 45 COPD patients was used. Lung macropahges had been stimulated with lipopolysaccharide (LPS), with or without the corticosteroid dexamethasone, and tumour necrosis factor (TNF)-α, interleukin (IL)-6 and chemokine C-X-C motif ligand (CXCL) 8 production was measured. RESULTS: There was no difference in the anti-inflammatory effects of corticosteroids when comparing group mean data of COPD patients versus controls. The inhibition of TNF-α and IL-6 was greater than CXCL8. The effects of corticosteroids varied considerably between subjects, particularly at lower corticosteroid concentrations. CONCLUSIONS: We confirm that overall corticosteroid sensitivity in COPD lung macrophages is not reduced compared to controls. The varied effect of corticosteroids between subjects suggests that some individuals have an inherently poor corticosteroid response. The limited suppression of lung macrophage derived CXCL8 may promote neutrophilic inflammation in COPD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12931-015-0260-0) contains supplementary material, which is available to authorized users.